A Data Analytics Suite for Exploratory Predictive, and Visual Analysis of Type 2 Diabetes - Vennela, Valiki Siri; swamy, Gachikanti; Raju, Yeligeti; Arjun, Nalikanti (Journal of Neonatal Surgery, 2025)
The availability of large volumes of electronic records of T2D patient data provides opportunities for application of big data analysis to gain insight into the disease manifestation and its impact on patients. Data science in healthcare has the potential to identify hidden knowledge from the database, re-confirm existing knowledge, and aid in personalising treatment. In this paper, we present a suite of data analytics for T2D disease management that allows clinicians and researchers to identify associations between different patient biological markers and T2D related complications. The analytics suite consists of exploratory, predictive, and visual analytics with capabilities including multi-tier classification of T2D patient profiles that associate them to specific conditions, T2Drelated complication risk prediction, and prediction of patient response to a particular line of treatment.The analyses provided in this document examine sophisticated data evaluation methods, which are possible resources for clinical and decision-making processes that may enhance the management of T2D.